Ultrafast outflows disappear in high-radiation fields. Issue 1 (29th January 2018) - Pinto, C; Alston, W; Parker, M L; Fabian, A C; Gallo, L C; Buisson, D J K; Walton, D J; Kara, E; Jiang, J; Lohfink, A; Reynolds, C S
Abstract: Ultrafast outflows (UFOs) are the most extreme winds launched by active galactic nuclei (AGN) due to their mildly relativistic speeds (∼0.1–0.3 c ) and are thought to significantly contribute to galactic evolution via AGN feedback. Their nature and launching mechanism are however not well understood. Recently, we have discovered the presence of a variable UFO in the narrow-line Seyfert 1 IRAS 13224−3809. The UFO varies in response to the brightness of the source. In this work we perform flux-resolved X-ray spectroscopy to study the variability of the UFO and found that the ionization parameter is correlated with the luminosity. In the brightest states the gas is almost completely ionized by the powerful radiation field and the UFO is hardly detected. This agrees with our recent results obtained with principal component analysis. We might have found the tip of the iceberg: the high ionization of the outflowing gas may explain why it is commonly difficult to detect UFOs in AGN and possibly suggest that we may underestimate their actual feedback. We have also found a tentative correlation between the outflow velocity and the luminosity, which is expected from theoretical predictions of radiation-pressure-driven winds. This trend is rather marginal due to the Fe xxv–xxvi degeneracy. Further work is needed to break such degeneracy through time-resolved spectroscopy.